The Authority Responsible Competent for Implementing Enforcement a Foreign Judicial Decision in Accordance with the Provisions of the Iraqi Court of Cassation - Muhamed, Fatima (Journal of Legal Sciences, 2025)
A foreign judicial ruling is not executed outside the territory of the court of the country that issued it by enforcement of law, but its implementation requires the intervention of the judicial or administrative authority in the requested state in respect of the principle of independence and sovereignty of the country. The latter undertakes the task of bringing down the ruling to apply repetition that benefits from the ruling issued in his service, and countries differ in determining the procedures followed to implement the foreign judicial ruling as well as they differ in determining the authority responsible for implementing a foreign judicial ruling. In Iraq, the Iraqi Court of Cassation hesitated in its successive provisions to determine the authority responsible for implementing a foreign judicial ruling, sometimes making this task the responsible of the Court of First Instance, which requires the interested party to establish a lawsuit for the purpose of implementing the ruling, and sometimes making the task of implementing the foreign judicial ruling of the responsibility of the implementation department to issue an implementation order, especially if the country from which the foreign judicial ruling was issued is a member of the Riyadh Convention on Judicial Cooperation of 1983.